5-year migration and inducible displacement of the uncemented LCS and ATTUNE rotating platform knee systems: a secondary report of a randomized controlled RSA trial - Raymond Puijk; Lennard A Koster; Bart G C W Pijls; Jiwanjot Singh; Marjolein Schager; Bart L Kaptein; Peter A Nolte (Acta Orthopaedica)
Background and purpose: Early migration of the uncemented cruciate-sacrificing rotating platform ATTUNE and Low Contact Stress (LCS) tibial components was classified as at-risk for aseptic loosening rates exceeding 6.5% at 15 years based on recent fixation-specific migration thresholds. In this secondary report of a randomized controlled trial (RCT) we aimed to evaluate whether the 5-year migration, inducible displacement, and the clinical outcome of the ATTUNE components were comparable to those of the LCS. Methods: Patients from the initial 2-year radiostereometric analysis (RSA) RCT were recruited for a 5-year follow-up. At 5 years, participants underwent 2 supine and 1 loaded RSA examination, clinical assessments, and questionnaires. Migration was analyzed using maximum total point motion (MTPM), translations, and rotations, focusing on 5-year migration, continuous migration (> 0.10 mm/year), and inducible displacement. Revisions, along with clinical and functional outcomes, were also evaluated. Results: At 5 years, 24 ATTUNE and 24 LCS implants were analyzed. The mean MTPM was similar for tibial components (ATTUNE 1.13mm [confidence interval (CI) 0.94–1.33]; LCS 1.24 mm [CI 1.05–1.46]) but significantly lower for the ATTUNE femoral component (1.14 mm [CI 0.92–1.39]) than LCS 1.87 mm [CI 1.57–2.21]). 2-to-5-year migration rates were comparable, but 11 ATTUNE and 7 LCS exceeded 0.10 mm MTPM/year, indicating a higher risk of loosening. Inducible displacement was similar, although 1 patient with a tibial ATTUNE showed excessive displacement (3.34 mm MTPM) with focal osteolysis but no symptoms. 1 revision 10 days post-surgery was performed for an ATTUNE insert spinout, resolved with an isolated insert exchange. Clinical and functional outcomes were comparable. Conclusion: At the 5-year follow-up, ATTUNE tibial components showed similar migration, while the femoral component migrated significantly less than the LCS, which mainly occurred during the first 2 years. 2-to-5-year migration rates, inducible displacement, and clinical and functional outcomes were comparable. These findings suggest a comparable long-term risk of aseptic loosening between the uncemented ATTUNE and LCS knee systems.